Moving Children and Adolescents - Reimers CD (Deutsche Zeitschrift für Sportmedizin)
Cerebral infarcts and haemorrhages, dementia, Parkinsons disease, sarcopenia, falls,and insomnia have in common that they frequently occur in higher ages, may considerably impair quality of life and cannot be primarily prevented by medication. Regular physical activity and sports however have the ability to reduce the risk of these diseases. In this review, mainly the results of corresponding meta-analyses are presented. The current knowledge indicates that the risk of ischaemic or haemorrhagic strokes can by reduced by about one fifth to one fourth, that of cognitive decline by about one fifth to one third, and that of Parkinsons disease by about one third.The effective risk reduction probably is somewhat higher, since in the meta-analyses of the prospective cohort studies the known so-called vascular risk factors such as arterial hypertension, diabetes mellitus, and dyslipidaemia, which also profit by physical activity, have been taken into account. The question of possible reverse causality has been discussed. The risk of a sarcopenia may be reduced by one third to almost a half. Regular exercise, especially balance training, reduces the risk of falls by one fifth to one half. Also sleep disturbances are less frequent in physical active as compared to inactive individual.KEY WORDS: Stroke, Dementia, Parkinsons Disease, Sarcopenia, Falls, Insomnia